The Crime of Corruption and How to Eradicate It - Amelia Wati; Ni Made Sawitri; Riva Aisabila; Sela Kurniati; Syafa Adinda; Ziyadatun Widad; Masduki Asbari; Dewiana Novitasari; Agus Purwanto (Journal of Community Service and Engagement, 2022)
The purpose of this article aims to find out the crime of corruption and how to eradicate it. corruption eradication activities in Indonesia can overcome the problem of corruption which has become an obstacle in the development of the country and can harm the country. So far, corruption is better understood by various parties, not eradicated, even though corruption is a type of crime that can touch various interests related to human rights, state ideology, economy, state finances, national morals, and so on, which are evil. How to eradicate corruption by using the webinar method to students through zoom meetings with students from a private university in Tangerang.